2018
DOI: 10.5761/atcs.cr.17-00092
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum Carcinoembryonic Antigen Concentration Caused by Everolimus-Induced Lung Injury: A Case Report

Abstract: A 66-year-old woman underwent right nephrectomy for treatment of renal cell carcinoma (RCC). Two years later, she underwent wedge resection of the right lung for treatment of metastatic RCC and primary adenocarcinoma of the lung. She began oral sorafenib for the remaining nodules of the left lung, which were suspected to be metastatic RCC. Two years later, the sorafenib was changed to everolimus because of slight enlargement of the left pulmonary nodules. The carcinoembryonic antigen (CEA) concentration then i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…CEA is considered a biomarker for SCLC and adenocarcinoma (AD) of the lung [29], and serum CEA is elevated in many types of cancers mostly in AD [30,31]. CEA is also increased in other types of non-cancerous diseases or other conditions [11,32]. Our results showed that high levels of CEA were observed in both NSCLC (which includes AD and SCC) and SCLC (Figures 1, 2A, 2B).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…CEA is considered a biomarker for SCLC and adenocarcinoma (AD) of the lung [29], and serum CEA is elevated in many types of cancers mostly in AD [30,31]. CEA is also increased in other types of non-cancerous diseases or other conditions [11,32]. Our results showed that high levels of CEA were observed in both NSCLC (which includes AD and SCC) and SCLC (Figures 1, 2A, 2B).…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, reports concerning the diagnostic performance of serum biomarkers on lung cancer were still inconsistent and debatable, thus the biomarkers are underutilized in clinical practice in general. Furthermore, the elevation of some of the biomarkers was found not only in lung cancer but also, they were detected abnormally in other diseases or conditions, making the specificity of the proposed biomarkers more concerned [8][9][10][11][12]. It is unclear whether gender and age have an impact on serum levels of lung cancer biomarkers, thereby interfering with the judgment in clinics.…”
mentioning
confidence: 99%
“…Komatsu et al . 9 reported that CEA rose from 12.2 to 25.7 ng/mL after everolimus treatment of a patient with metastatic renal cell carcinoma; CEA declined to 5.9 ng/mL 2 months after discontinuation of everolimus. The authors believe that this was due to everolimus causing grand glass opacities in bilateral lungs.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the report of elevated serum carcinoembryonic antigen (CEA) following everolimus administration, 1 ) in which it was reported that everolimus treatment for renal cell carcinoma with lung metastasis caused pulmonary ground-glass opacities accompanied by elevated serum CEA. Furthermore, interrupting everolimus resulted in improvements of both lung shadows and elevated CEA levels.…”
mentioning
confidence: 99%